Assessing Land Degradation and Vegetation Cover in Parwan Province Using GIS and Remote Sensing - Safi, Lutfullah; Mujeeb, Mujeebullah; Hashimi, Sayed Mohammad Tamim (Journal of Natural Sciences – Kabul University, 2026)
Afghanistan is facing severe environmental crises and land degradation that have significantly impacted land quality, biodiversity, ecosystems, and land productivity. Therefore, this study assessed the level of land degradation and vegetation cover in Parwan Province. This study used remote sensing data to investigate key variables of land degradation. The results show that land degradation in Parwan province has increased rapidly in recent years. Soil organic carbon (SOC), which reflects climate pressure on vegetation's capacity to retain soil cover, has decreased. Precipitation has decreased in Parwan, and a negative relationship has been found between NDVI and rainfall. The increase in NDVI levels is due to global warming, so conservation practices are necessary to address the problem, such as agroforestry, rangeland management, sustainable agriculture, and smart agriculture.